(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
The physicochemical properties, fatty acid composition, aflatoxin contamination and heavy metals of extracted mango kernel oils of four Bangladeshi varieties (Langra, Gopalbhog, Khirshapat & Amrupaly) were studied. The results were compared with published values of CIR expert panel, Indian Standard of Mango Kernel Fat, Scientific Commission of the European Community and US Food and Drug Administration (FDA). The estimated values of aflatoxin B1and total aflatoxins were 1.45809 ppb and 5.14761ppb respectively which were lower than the limit levels of European Community (2 ppb for aflatoxin B1) and US FDA (20ppb for total aflatoxins value). Heavy metals like arsenic & lead concentration were found 0.034 & 0.45 ppm respectively which were lower than the value of Indian Standard of Mango Kernel Fat; 9231 (1979) (0.5 & 5.0 ppm respectively). In fatty acid composition; palmitic acid, stearic acid, arachidic acid, oleic acid and linoleic acid were within the range of CIR expert panel reported values. Bangladesh J. Sci. Ind. Res. 52(1), 43-48, 2017